2014
DOI: 10.5539/ies.v7n6p128
|View full text |Cite
|
Sign up to set email alerts
|

Writing Anxiety as a Predictor of Writing Self-Efficacy in English for Special Education Arab Learners

Abstract: The study aimed at investigating the relationship between writing anxiety and writing self-efficacy in English for special education Arab learners of English. It also investigated the use of writing anxiety scores as a predictor of writing self-efficacy. In addition, it explored differences between males and females in both writing anxiety and writing self-efficacy in English. The sample of the study consisted of 90 intermediate school students in the state of Kuwait (47 males and 43 females); the mean age was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 7 publications
1
9
0
1
Order By: Relevance
“…In this case, her writing self-efficacy led to failure to write and a stressful writing experience. This finding supports others in literature that self-efficacy and anxiety are related (Salem & Al Dyiar 2014;Öztürk & Saydam, 2014) but what is stressed here is that such a relationship is not a simple direct cause and effect. Rather, it is a complex multi-directional relationship where writing self-efficacy can be the cause and the effect.…”
Section: Now I Am Sure I Can Write In Different Topics (Diana Journasupporting
confidence: 80%
See 1 more Smart Citation
“…In this case, her writing self-efficacy led to failure to write and a stressful writing experience. This finding supports others in literature that self-efficacy and anxiety are related (Salem & Al Dyiar 2014;Öztürk & Saydam, 2014) but what is stressed here is that such a relationship is not a simple direct cause and effect. Rather, it is a complex multi-directional relationship where writing self-efficacy can be the cause and the effect.…”
Section: Now I Am Sure I Can Write In Different Topics (Diana Journasupporting
confidence: 80%
“…When students" anxiety level rose, their writing self-efficacy declined to a moderate level. L2 writing anxiety is thought to predict L2 writing self-efficacy, with a negative correlation found between these two variables (Salem & Al Dyiar, 2014). Individuals are believed to expect success when they feel less anxious and stressed (Bandura, 1977).…”
Section: Self-efficacy and L2 Writingmentioning
confidence: 99%
“…These sub-categories are cognitive anxiety, avoidance behavior, and somatic anxiety. Salem and Al Dyiar (2014) investigated writing anxiety in relation to writing self-efficacy and found that the relation between writing anxiety and writing self-efficacy was more pervasive with male students. As for the causes of writing anxiety, Abdel-Latif (2007) iterated the factors that lead to Egyptian English major students writing anxiety and low writing self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Writing is one of the important skills in students' English learning (e.g., Rintaro, 2012). However, teaching writing is one of the most demanding jobs for English as a foreign/second language (EFL/ESL) teachers as it includes several practices that require writing teachers to dedicate much time to assisting students to write better (Salem & Abu Al Dyiar, 2014). The help that other people give to someone in the process of writing is called feedback, and feedback given by a teacher is called teacher feedback.…”
Section: Introductionmentioning
confidence: 99%